Lendo mulheres : empoderamento de sertanejas através de leituras - Rocha, Ivânia Nunes Machado (2022)
This thesis is situated in the cultural field of studies and ethnographic analysis, with emphasis on literary criticism and feminist criticism. This is a research on female reception and empowerment based on a reading course of works by black and/or northwestern female writers given to country women of Irecê/BA, focusing on their reception processes, considering the subjective aspects of the feminine identities. The course had a duration of 180 hours, with presential meetings and complemented by previous individual readings and interactions by social networks, within a collaborative learning system. Therefore, we used five theoretical axis: reading/reception, literature and culture; gender and feminisms; identity, locus of speech and dislocations/micro-policies; intersectionalities between gender, class, race; reading and literary literacy. This investigative approach is relevant from the point of view of the thematic and the research subjects, since it comes about books/texts and female authors little known to the country women, since they are not canonical works, nor are they disseminated by the hegemonic media platforms. The reception process aimed to analyze personal narratives of the participants and the impact of the readings of female authorship’s texts in the critical formation of these women, as well as the empowerment and the change of horizons of gender expectations of these country women. The critical readings went through the subjectification of political positioning of the participants in relation to the feminine condition, in order to combat racisms, sexisms, and subalternities naturalized in society, but questioned in the selected works. The methodology employed was the literature revision plus the field research, in a decolonial and deconstructive perspective, employing approaches linked to gender questions, women and feminism, as well as that of race, class and ethnicity and geographical location form the feminist perspective proposed by Djamila Ribeiro, Carla Akotirene, Joice Berth, Heloísa Buarque de Hollanda and others. The main strategy was the realization of an extension course denominated “Lendo Mulheres” (Reading Women), in which we worked with 18 students, through of critical works, we analyzed the implications of these reading on the collaborators’ lives. The results point to the effective transformation that critical reading may operate on country women, collaborating for their awareness as subjects of knowledge and encouraging them to take their locus of speech as women, northwesters and country women, with a skin color consisting mostly of the colors black and brown; and empowering them, form the point of view of knowledge, as for them to exercise their autonomy and their search for freedom and more favorable existential conditions to their human and personal development.